СOMMUNICATION STRATEGY DEVELOPMENT ALGORITHM FOR B2C STARTUPS - Verbytska, Anna; Babachenko, Larysa (Pryazovskyi Economic Herald, 2021)
This article proposes an author's algorithm for developing a communication strategy for B2C startups, including: communication audit of B2C startup, setting goals and objectives of the communication strategy (business goals, marketing goals, communication goals); analysis of the business model of the startup (defining of the life cycle of the startup); defining of the target audience; development of communication messages for each segment in accordance with the profile; definition of startup communication tools; definition of communication channels of the startup; development of a communication plan; media plan development; evaluation of the effectiveness of the communication strategy. The proposed algorithm focuses on the in-depth analysis of the profile of the consumer's personality, which allows to predict behavioural responses in conditions of uncertainty and create an effective communication strategy B2C startup.